Penerapan Model Pembelajaran Problem Posing Untuk Meningkatkan Konsep Berpikir Matematis Siswa Kelas X SMK Muhammadiyah Kartasura Tahun Ajaran 2016/2017 - Darma, Eny Choriah Putri, Drs. Ariyanto, M.Pd (2017)
The purpose of this research is to improve students' mathematical thinking concept by applying Problem Posing approach. This research is a Classroom Action Research (CAR). The subject that receive the action is grade X M.B of Muhammadiyah Vocational High School of Kartasura. The number of students of grade X M.B are 33 students. The data collection techniques are observation, field notes, test and documentation. Based on the research analysis it can be concluded that the application of Problem Posing approach can improve the mathematical thinking concept of student grade X M.B. It can be seen from the increase in the precentage of the indicators of mathematical thinking concept of student's, namely 1) the ability to understand the mathematical problem of a prior act of from 28.57% increase to 90%, 2) The ability of students to solve problems with the mathematical concept of a prior act of from 33.33% increased to 87.09%, and 3) The ability of students to draw conclusions appropriately as much as 24.24% increased to 77.41%. It can be concluded that the application of Problem Posing learning model can improve students' mathematical thinking concept.